Modeling Evaluation of Tidal Stream Energy and the Impacts of Energy Extraction on Hydrodynamics in the Taiwan Strait - Ming-Hsi Hsu; Wei-Bo Chen; Wen-Cheng Liu (Energies, 2013)
Tidal stream speeds in straits are accelerated because of geographic and bathymetric features. For instance, narrow channels and shallows can cause high tidal stream energy. In this study, water level and tidal current were simulated using a three-dimensional semi-implicit Eulerian-Lagrangian finite-element model to investigate the complex tidal characteristics in the Taiwan Strait and to determine potential locations for harnessing tidal stream energy. The model was driven by nine tidal components (M2, S2, N2, K2, K1, O1, P1, Q1, and M4) at open boundaries. The modeling results were validated with the measured data, including water level and tidal current. Through the model simulations, we found that the highest tidal currents occurred at the Penghu Channel in the Taiwan Strait. The Penghu Channel is an appropriate location for the deployment of a tidal turbine array because of its deep and flat bathymetry. The impacts of energy extraction on hydrodynamics were assessed by considering the momentum sink approach. The simulated results indicate that only minimal impacts would occur on water level and tidal current in the Taiwan Strait if a turbine array (55 turbines) was installed in the Penghu Channel.